Freedom Of Speech And Institutional Crisis: Content Analysis Of Youtube Comment Columns In The Sukatani Band Case - Rahman, Hafis; Nasvian, Moch Fuad (Universitas Negeri Yogyakarta, 2025)
The various public reactions that appeared in the comments section of the video about the song “Bayar Bayar Bayar” by the band Sukatani illustrate how the public perceives the image of the police institution today, as well as freedom of expression in Indonesia. Based on this, the content of the comments section is an important source of data for understanding the current image of the police and the implementation of democracy in Indonesia. This study employs content analysis methodology, with data collected from the comment sections of five YouTube channels. From these five channels, 24 videos were selected for analysis, chosen through purposive sampling based on the criteria of high credibility and discussions related to the Sukatani band between February 21–24, 2025. The results of this study reveal that netizens believe the practices described in the song lyrics “Bayar Bayar Bayar” are indeed occurring. Based on this, the police institution is currently in a paracrisis phase that could escalate into a full-blown crisis at any time. Additionally, the study found that netizens perceive the police institution as being resistant to criticism. The various criticisms of the police institution that appear in the comment sections reflect democracy itself, but the implementation of democracy has not yet been institutionalized, given the ongoing allegations of intimidation against the Sukatani band for criticizing the police.